PKM Penerapan Digital Teknologi Produksi dan Pemasaran Madu Untuk Meningkatkan Daya Saing Peternak Lebah Madu di Kabupaten Kebumen - Harini Abrilia Setyawati; Larasati Puspita Saridewi; Ika Neni Kristanti (JURPIKAT, 2026)
In the digital age, information and communication technology (ICT) has become a major catalyst in the transformation of various industrial sectors, including beekeeping. The application of digital technology in production and marketing processes can open new opportunities for beekeepers to enhance efficiency, product quality, and competitiveness in an increasingly competitive market. With these improvements, beekeepers can compete more effectively in both local and national markets. Therefore, it is important to explore and implement digital technologies that can support beekeepers in increasing their productivity and competitiveness. Overall, the adoption of digital technology in honey production and marketing has made a significant contribution to enhancing the competitiveness of honey products.